Impact of COVID-19 and green finance on transportation energy carbon emissions in China: From the perspective of an automobile energy consumption structure - Liu, Lingyun; Cheng, Yanxin; Guan, Ningning; Liu, Yazhen; Zhang, Xin; Li, Yang; Yang, Zining (Frontiers in Environmental Science, 2023)
The transportation sector is the main source of energy consumption and carbon emission in China. The new energy vehicles produced under technological change is conducive to achieving carbon peak for transportation sector. This paper gets the data of auto consumption and green finance indices of 30 Chinese provinces and cities from 2016 to 2020 through the Web-Crawler, and construct a Regression Discontinuity (RD) model to test the effect of epidemic shock and green finance development on the reduction of transportation energy carbon emissions. The results show that the COVID-19 epidemic shock can change people's consumption preferences and reduce carbon emissions of transportation energy. Green finance can further effectively contribute to the carbon emission reduction of transportation energy during the outbreak, but the overall mitigation effect is limited. The empirical evidence based on the macro level is helpful to assess the long-term impact of the COVID-19 epidemic on transport energy carbon emissions and constructive for supporting transport energy carbon emission reduction with green finance.